Subclinical Hypothyroidism and Its Association with Increased Cardiovascular Mortality - Alvaro Altamirano Ufion; Beenish Zulfiqar; Abdalla Hassan; Roshanak Habibi; Prajwal Boddu (Cardiology Research and Practice)
Thyroid hormones play an important role in regulating different metabolism functions and multiple organs’ performance. Changes in the thyroid hormone axis can lead to profound effects on the stability of vital organs and systems, especially the cardiovascular system. Hypothyroidism is classified according to the clinical presentation as overt and subclinical. There is some evidence supporting the benefits of thyroxine hormone replacement for subclinical hypothyroidism on cardiovascular mortality outcomes. However, the clinical relevance of measuring and treating high thyroid-stimulating hormone (TSH) levels in newly diagnosed heart failure patients with preserved ejection fraction requires further study. In this report, we review the current evidence regarding the prognostic significance of subclinical hypothyroidism in heart failure patients with preserved ejection fraction.